PELAPORAN KEBERLANJUTAN SEBAGAI TANTANGAN BAGI PENGUKURAN KINERJA KEUANGAN, TATA KELOLA PERUSAHAAN SERTA UKURAN PERUSAHAAN - Azwani Aulia (LPPM UNIBI, 2021)
A sustainability report is a report made by a company that is useful for internal and external parties of the company, because this report is used as a company communication tool in disclosing company activities that are not only focused on profit, but also planet & people, as a form of feedback in responding to needs. all stakeholders and provide confidence that the company can maintain its business sustainability. This study aims to determine the effect of corporate governance, company size, financial performance on sustainability reporting either partially or simultaneously. This type of research is quantitative with a descriptive approach. The results showed that simultaneously ROA, DER, company size and corporate governance had an effect on sustainability reporting. While partially shows that return on assets, debt to equity ratio and firm size affect the quality of sustainability report disclosure, while the audit committee and managerial ownership have no effect on sustainability reporting.